Community Participation in Forest Management Programs in Azad Jammu Kashmir and Hazara, Pakistan - Mohamad, Mamoona Wali (2009)
Participatory forest management (PFM) initiatives have been in place in Pakistan for almost three decades, but apparently there have not been any visible impacts. The goal of this study was to evaluate two participatory forest management (PFM) programs, namely Integrated Land Management (ILM) and Participatory Watershed Management (PWSM), by assessing the levels of participation, factors influencing participation and the impacts of these programs on the socioeconomic conditions of local people and forest/watershed resource development. A multistage random sampling technique was applied to select units of analysis, households (respondents). The total sample drawn was 1,817 units, 1,479 from the program sample group and 338 from the no-program group. A structured questionnaire was used in face to face interviews to collect research data. However, qualitative data collected through informal discussions, group meetings, and focus groups were used to subjectively support the results of the quantitative data. The social, economic and forest resources impacts were assessed using different statistical analyses. The levels of participation of participants, forms of participation with reference to programs, and socio-demographic characteristics of participants and non-participants were measured using a three dimensional framework and Participants’ Participation Index (PPI).